Review Articles: A Critical Review of the Pitfalls and Guidelines to effectively conducting and reporting reviews - Mpofu, Favourate Y (Technium Social Sciences Journal, 2021)
One of the most fundamental building blocks of any research activity is available knowledge in the subject or area being investigated. Therefore, how to appropriately access, assess, decipher, analyse and synthesise information from this body of knowledge should be an important consideration for researchers. A properly structured, conducted and well reported literature review can build a powerful foundation for strengthening knowledge and advancing theoretical or conceptual framework development. The integration of research outcomes and perspectives from diverse studies can help pinpoint consistencies and inconsistencies, research gaps and address research questions in a cogent manner. Despite reviews being a necessity, how to do them effectively, transparently and constructively remains a complicated task. In light of this observation, literature review as a research methodology dimension is vital, yet researchers often find their review articles being rejected for publication. The study found out that common pitfalls that lead to rejections include: poor article quality, no visible methodology and unclear contribution or lack of value addition. Possibly, researchers are not offering, adequate information on the research strategy, inclusion and exclusion criteria for studies used, the research process and analysis. This study was motivated by this rejection dilemma and sought to contribute to research literature on how to enhance the quality, validity and trustworthiness of review research. Through a critical literature review, the paper discusses the probable contribution of review articles, challenges of conducting them productively and possible amelioration guidelines.